The Effect of Skepticism, Time Pressure, and Remote Audit During the COVID-19 Pandemic on Audit Quality: A Study of Auditors’ Perception - Saputro, Kristiyanto Bayu; Mappanyukki, Ratna (Badan Pemeriksa Keuangan Republik Indonesia, 2022)
This study aimed to determine the impact of professional skepticism, audit time pressure, and remote audit during the COVID-19 pandemic on audit quality and the effect of remote audits on the relationship between professional skepticism and audit quality. The study was conducted through a questionnaire survey to The Audit Board of The Republic of Indonesia (BPK RI) auditors and analyzed using Smart PLS quantitative analysis methods. The results showed that professional skepticism, audit time pressure, and remote audit affected audit quality. Meanwhile, the remote audit does not moderate the relationship between professional skepticism and audit quality, classified as predictor moderation.